2017
DOI: 10.22159/ijcpr.2017v9i5.22138
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antioxidant Activity of Methanolic Extract of Leaves of Corchorus Olitorius

Abstract: Objective: The present study was carried out to evaluate the in vitro preliminary phytochemical analysis and antioxidant activity of methanolic leaf extracts of Corchorus olitorius L. The in vitro antioxidant activity was evaluated by DPPH radical scavenging activity method.Methods: Fresh jute leaves (immature, mature and senescence) were collected, air dried and the crude powder was prepared for phytochemical and antioxidant analysis. The powder was mixed with 70% methanol and the supernatant was separated. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 1 publication
3
11
1
Order By: Relevance
“…The traditional medicinal use of the plant in Egypt and India dates back to some 2500 years, where it was used to treat fever, diarrhea and vomiting (Islam, 2012). The antioxidant and analgesic activities of the plant leaves have been reported by Sadat, et al, (2017) and Ipav et al (2018). In Nigeria, bush okra C. oliterius is consumed by almost every ethnic group, especially in South-West, North Central and Northeastern Nigeria.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The traditional medicinal use of the plant in Egypt and India dates back to some 2500 years, where it was used to treat fever, diarrhea and vomiting (Islam, 2012). The antioxidant and analgesic activities of the plant leaves have been reported by Sadat, et al, (2017) and Ipav et al (2018). In Nigeria, bush okra C. oliterius is consumed by almost every ethnic group, especially in South-West, North Central and Northeastern Nigeria.…”
Section: Introductionmentioning
confidence: 80%
“…Phytochemicals are known to function as immunomodulators and may exhibit antioxidant, anti-inflammatory, anticancer, antimalarial and antimicrobial properties (Sadat et al, 2017). Phytochemicals are also referred to as phytonutrients and are classified according to their chemical structures and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical screening showed that the rhizomes of A. africana contain secondary metabolites, in particular triterpenes, tannins, flavonoids, saponins, phenolic compounds (Table 1). These phytochemicals possess therapeutic activity that could justify its uses as traditional medicine [23].…”
Section: Discussionmentioning
confidence: 99%
“…They play an important role in prevention and treatment of chronic diseases including inflammatory processes. It has been known that plant steroid, flavonoids, tannins, and phenols are antioxidants [23,30]. [31,32] have indicated that more than one the measurement of antioxidant capacity is necessary for take into account the different antioxidant modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results differ from those of some authors such as Qorina et al, (2019) who demonstrated the presence of alkaloids and gall tannins from the extract of Annona muricata leaves using other solvents (ethanol, methanol, n-hexane and ethyl acetate). In addition, the presence of alkaloids is also noted in the methanolic extract of the leaves of Corchorus olitorius (Sadat et al, 2017). These secondary metabolites have many biological and therapeutic properties.…”
Section: Qualitative Phytochemical Screeningmentioning
confidence: 99%